∫ − 1 3 ( x + 1 ) ( 3 − x ) d x = π c , c = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Simple good problem. Usually I've seen jee problems require a small tricky generalization. Then u can solve any integral.
This is helpful for such type of problems:
(
x
−
a
)
(
x
−
b
)
=
(
x
−
2
a
+
b
)
2
−
(
2
a
−
b
)
2
Problem Loading...
Note Loading...
Set Loading...
Motivation : After thinking for a while and looking at the problem this general form comes to mind: ∫ a 2 − x 2 d x because of the presence of the square root. Now,we want to convert ( x + 1 ) ( 3 − x ) into the form a 2 − x 2 ,we can do this by writing one of the two factors in the from ( a − z ) and the other in the form ( a + z ) where z is a linear function in x and a a constant.We see that the sum of the two factors is 2 a = 4 ⟶ a = 2 hence we get that z = x − 1 because then the two factors would become z + 2 and 2 − z and d x = d z ,so the integral becomes, ∫ − 2 2 2 2 − z 2 d z = sin − 1 ( 2 z ) ∣ − 2 2 = 2 × sin − 1 1 = 2 × 2 π = π .And done!